Nils Petter Gleditsch and Olav Njølstad (eds.), Arms Races: TechnologicalandPolitical London, Newbury Park, CA and New Delhi: Sage Publications Ltd., 1990, 424 s. - Michael Pilgaard, Peter (Politica, 1990)
-